THE USE OF ANTHROPONYMS IN ZAVKI’S WORK (Scientific journal of the Fergana State University, 2024)
This article analyzes the use of anthroponyms in Ubaydulla Solikh oglu Zavqi’s works. The anthroponymic units: names, nicknames, nicknames are classified and the poet's skill as a nominator is revealed. Names are divided into lexical-semantic groups and their meaning is explained. The etymological analysis of some names serves to express how the onomastics of the Uzbek language is reflected in Zavki’s work.